(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
There is much evidence that the ABO blood group system may play a role in the pathogenesis of the disease. The relationship between ABO and Rhesus blood groups and cancer risk has been demonstrated in many research works. However, concerning gynaecological malignancies, these findings are inconsistent. This study aimed to evaluate the frequency of ABO and Rh-D blood groups in patients with carcinoma cervix. This cross-sectional study was conducted in the Department of Transfusion Medicine, Department of Gynaecological Oncology and Department of Pathology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. A total of 110 clinically suspected cervical cancer patients were included in this study. Pap smear tests was done in all cases and the patients were divided into case (Pap test positive) and control group (Pap test negative). A total of 55 patients were included in each group. Blood groups (ABO & Rh-D) of all the patients were recorded. A higher number of the patients in the cervical cancer group were multiparous than in the control group. Almost in two-thirds of the population, the age of marriage was <18 years in the cervical cancer group compared to 34.5% in the control group. More than one-third population had “O” blood group in the case group, while it was 31% in the control group. The almost equal number had Rh D+ve in the case and control (92.7% vs. 94.5%). The differences between the blood group and Rh D were not statistically significant between the two groups. Nearly half (40.0%) of the participants had used a hormonal contraceptive in the case and 61.8% in control. The differences in hormonal contraceptives use were statistically significant within the two groups. The distribution of “O” blood group and Rh D +ve cases was found to be higher in patients with cervical cancer than in non-cancer patients although the difference was not statistically significant. BSMMU J 2022; 15(2): 70-74